Presenting the model of antecedents affecting moral-emotional acting in education - arefeh kazemi malekmahmoudi; negin jabbari; kiomars niaz azari (مدیریت و چشم انداز آموزش)
AbstractThe aim of the current research is to identify and rank the antecedents affecting moral-emotional acting in education. This research was applicable in terms of its purpose, and was carried out with a quantitative approach with an exploratory design. The research method was descriptive-survey. The statistical population in the quantitative section included education managers of Golestan province; by stratified random sampling method, as many as 270 people. The research data collection tool included a researcher-made questionnaire, and data analysis was done through exploratory and confirmatory factor analysis in SPSS21 and PLS software. The results showed that the antecedents affecting moral-emotional acting have 2 dimensions: "individual antecedents and organizational antecedents". Individual antecedents have 3 components: "knowledge and information, personality traits, and motivation", and organizational antecedents have 4 components: "organizational culture, ethical atmosphere of the organization, organizational structure, and leadership and management". Considering the factors affecting moral-emotional acting, we can observe the growth of positive organizational behaviors and the institutionalization of ethics in the organization. According to the obtained model, there is a relationship between the exogenous variables of antecedents affecting emotional acting and the endogenous variable of emotional acting, based on the factorial path coefficients of 0.680; also according to the t-value, the effect of antecedents affecting emotional acting has become significant; therefore, there is a positive and significant relationship between the antecedent variables affecting emotional acting and emotional acting. Thus, it can be concluded that; the effect of effective antecedents on emotional acting is positive and meaningful.Extended abstractIntroductionThe present age is the age of organizations, and the custodians of these organizations are human beings; on the other hand, emotional acting is inevitable in work environments and people in jobs whose careers depend on high social interactions are forced to hide their real feelings in some cases, and reveal the expected feelings in the profession (Lu & Guy, 2018). Research has also shown that all kinds of emotional acting strategies can increase the psychological stress of employees and this stress can lead to negative results such as job dissatisfaction and burnout. Many researchers have confirmed the role of emotional acting strategies in the occurrence of job burnout. On the other hand, emotional acting is related to job satisfaction. Noting that educational centers are one of the most important custodians of learning in the country's educational system, it is necessary for these centers to have the category of antecedents affecting emotional acting, which refers to the management and expression of feelings and emotions in the workplace. Considering the essential importance and necessity of emotional acting, goals and strategies; the targeting and development of this in educational affairs can have an impact on the ever-increasing and all-round development, and should be operationalized in the form of an efficient and practical model (Nixon et al, 2020). Now, based on the research done and considering the importance of the effect of emotional acting on many variables in the work environment, it becomes necessary to examine the factors affecting emotional acting; and on the other hand, considering the lack of previous research related to the subject and such research necessity in educational organizations increases the importance of doing this research. Since one of the most important, most effective and most extensive social organizations responsible for selecting and transferring cultural elements to the new generation of society is the education organization of each country (Ensafdaran et al, 2017); this organization is a device that is also considered as the general model of the official institutions and organizations of the society, and has played a constructive and essential role in the survival and continuity of human culture and civilization since a long time ago. The education organization is very important from the social, cultural, and economic point of view as well as providing the basis for human development and growth. From a social point of view, sociologists define education as a means of managing and controlling society, and consider it the factor of survival and durability of civilizations, and believe that human skills have increased to an unimaginable extent of the collection of knowledge, and human communication has become more complicated (Kang & Jang, 2022). Therefore, taking into account that emotional acting is the behavior derived from the goals of the organization in order to express the appropriate emotions of employees during work; as a result, it is necessary to address the category of emotional acting in education and finally, this research can be a model for similar researches in other organizations and industries. Also, each research, while being based on previous studies, can in turn contain new findings and data and be a prelude to conducting subsequent studies.Considering the above, this research has tried to find out the main components of emotional acting by examining the characteristics of emotional acting through semi-structured interviews. Therefore, achieving this goal requires developed human resources in the future. Thus, in order to realize this ideal goal, education requires the training of human resources according to the needs of the society; human resources that can express appropriate emotions while working according to the goals of the organization. Therefore, in this research, we tried to answer this question: What is the appropriate model of antecedents affecting emotional acting in education in Golestan province?Theoretical literature- Antecedents affecting emotional acting: includes factors affecting management and planning to control and develop skills to express emotions according to the rules of the organization (Ensafdaran et al, 2017).- Education: It is an educational organization responsible for the education of children and teenagers as well as the training of teachers (Hyati et al, 2023).Kang & Jang (2022) conducted a research titled emotional labor of frontline employees towards their colleagues: the mediating role of team members' exchanges. In this research, the relationship between emotional labor of employees towards their colleagues and turnover intention was investigated by mediating the exchanges and supervisory listening, and the results showed that the relationship between employees' emotional labor towards their colleagues and the intention to leave the job is moderated by team member exchange, but the moderating effect of supervisory listening was found between surface action towards colleagues and team member exchange.Nixon et al, (2020) in a research aimed at investigating the effect of collective values ​​(culture) at the national and individual level on emotional acting strategies and employee pressure, emotional stress, turnover goals, job satisfaction and organizational commitment showed that collective values (culture) directly and reciprocally affect the emotional acting process model. Collective values ​​(culture) were associated with higher emotional actor engagement and lower employee pressures.Research methodologyThe method of the present research is applicable in terms of its purpose, and quantitative in terms of the method of data collection. In the first stage, through a qualitative study, the indicators of moral-emotional acting were identified.The statistical population of the research in the quantitative stage includes all education managers of Golestan province, including the heads of the general administration and their deputies, the heads of departments and their deputies, and the school principals and deputies, whose number was 902; using the method A stratified random sample, 266 people was selected for investigation.The research data collection tool was a researcher-made questionnaire included 51 closed-ended items based on a five-point Likert scale. It measures 2 dimensions: "individual antecedents and organizational antecedents", and 7 components: knowledge and information, personality traits, motivation, organizational culture, organizational ethical climate, organizational structure, and leadership and evaluates management. Data analysis was done in the quantitative section using exploratory and confirmatory factor analysis in SPSS22 and PLS statistical software.Research findingsIn the quantitative part, exploratory factor analysis was used to identify antecedents. Kaiser-Meyer-Elkin and Bartlett proportionality tests were used to determine the adequacy and necessary conditions of the data to perform factor analysis. The findings showed that at the confidence level of 95% and the measurement error of α = 5%, the value of the KMO statistic was calculated to be more than 0.7.According to the special values, 3 factors are extracted; because they have special values ​​greater than one. The percentage of explained variance in the last column shows that if 3 factors are extracted, 83.838% of the changes in the questions can be explained by the extracted factors.Based on the results, it was determined that; the dimension of personal antecedents has 3 components: "knowledge and information, personality trait, and motivation", which the highest factor loading (0.928) related to question 19, and the lowest factor loading (0.699) related to question 3.According to the special values, 4 factors are extracted; because they have special values ​​greater than one. The percentage of explained variance in the last column shows that if 4 factors are extracted, 77.537% of the changes in the questions can be explained by the extracted factors.Based on the results, it was determined that; the dimension of organizational antecedents has 4 dimensions "organizational culture, organizational moral atmosphere, organizational structure, and leadership and management"; which the highest factor load of 0.893 related to question 28, and the lowest factor load of 0.728 related to question 7.Discussion and conclusionThe general results of the research showed that the antecedents affecting moral-emotional acting have 2 dimensions "individual antecedents and organizational antecedents". Individual antecedents have 3 components "knowledge and information, personality traits and motivation", and organizational antecedents have 4 components "organizational culture, ethical atmosphere of the organization, organizational structure and leadership and management". It can be said that the education system needs managers who are effective actors in the direction of excellence in the management of the education system, and the tendency of the education system should be to employ such people. Ethical-emotional acting has significant effects on various organizational processes. It should be mentioned that when organizations are designed, sometimes people are ignored and most of the focus and attention is placed on its structure and design; while organizations need to design a proper structure as much as they need to achieve the set goals, they also need the moral-emotional acting of their employees. Considering that the education organization is the largest social organization in the heart of the society, which uses huge human and financial resources for the education of students every year, it should use efficient human resources to show appropriate behavior and feelings, and respect the ethics of behavior with others who can provide the highest quality services according to the dignity of people.